1997
DOI: 10.1523/jneurosci.17-05-01720.1997
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Selective Auditory Responses in the Superior Colliculus of the Echolocating Bat

Abstract: When a bat approaches a target, it continuously modifies its echolocation sounds and relies on incoming echo information to shape the characteristics of its subsequent sonar cries. In addition, acoustic information about the azimuth and elevation of a sonar target elicits orienting movements of the head and pinnae toward the sound source. This requires a common sensorimotor interface, where echo information is used to guide motor behaviors.Using single-unit neurophysiological methods and free-field auditory st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 45 publications
3
52
0
Order By: Relevance
“…Because of the large spatial receptive fields of delay-tuned neurons, they do not seem to be suited to process directional information of echoes in the AC of the mustached bat (Suga et al 1990). In the midbrain superior colliculus of E. fuscus, however, Valentine and Moss (1997) found that responses of delay-tuned neurons depended not only on the temporal delay between pulse and echo, but also on the direction of stimulation. They could show that the best delay of all delay-tuned neurons changed with the azimuthal position of sound presentation.…”
Section: Neural Coding Of Abstract Echoesmentioning
confidence: 89%
See 1 more Smart Citation
“…Because of the large spatial receptive fields of delay-tuned neurons, they do not seem to be suited to process directional information of echoes in the AC of the mustached bat (Suga et al 1990). In the midbrain superior colliculus of E. fuscus, however, Valentine and Moss (1997) found that responses of delay-tuned neurons depended not only on the temporal delay between pulse and echo, but also on the direction of stimulation. They could show that the best delay of all delay-tuned neurons changed with the azimuthal position of sound presentation.…”
Section: Neural Coding Of Abstract Echoesmentioning
confidence: 89%
“…Delay-tuned neurons, sensitive to certain pulse-echo delays, have been found in the midbrain (Dear and Suga 1995;Portfors and Wenstrup 1999;Valentine and Moss 1997), thalamus (Olsen and Suga 1991;Wenstrup 1999), and AC (Dear et al 1993;Feng et al 1978;Hagemann et al 2010;Suga et al 1990;Sullivan 1982) of different bat species. Because of the large spatial receptive fields of delay-tuned neurons, they do not seem to be suited to process directional information of echoes in the AC of the mustached bat (Suga et al 1990).…”
Section: Neural Coding Of Abstract Echoesmentioning
confidence: 99%
“…Two populations of neurons have been identified in the superior colliculus of the big brown bat (E. fuscus), one that responds selectively to acoustic stimulation at a particular azimuth and elevation (2D neurons) and one that responds selectively to acoustic stimulation over restricted azimuth, elevation, and distance (3D neurons) (38). The population of 2D neurons responds to single frequency-modulated (FM) signals and would be well suited for passive localization of sound sources but not for precise distance measurements required for prey capture.…”
Section: Discussionmentioning
confidence: 99%
“…In a variety of species there are topographic representations of sensations that also register appropriately with tectal motor maps. These include electroreception in weakly electric fishes (Bastian, 1982), thermosensation in rattlesnakes (Hartline et al, 1978), echolocation in bats (Valentine and Moss, 1997), audition in barn owls (Knudsen, 1982) and somatosensation in cats (Stein et al, 1976). While less is known about other sensory inputs to the zebrafish tectum, given the conserved nature of tectal organization it is likely a similar coregistration of different sensory modalities exists.…”
Section: Importance Of Vision During Prey Capturementioning
confidence: 99%